Evaluation of the neuroprotective activity of P. amarus in attenuating arsenic-induced neurotoxicity - an in vivo study - A. Hashim; Mohammed Gulzar Ahmed; Nabeel Beeran Abdul Rahiman; Shyamjith Manikkoth; K. Leena Pramod (Phytomedicine Plus, 2022)
Background: Arsenic is viewed as a bizarre and frightful element in human history. Recent studies showed that even low levels of arsenic can cause neurological damage. Phyllanthus amarus is an important medicinal herb proved to have neuro protective effect in experimental animals. This pre-clinical study used an animal model of arsenic toxicity and screened the different neuroprotective mechanisms of Phyllanthus amarus ethanolic extract. Purpose: To assess the effect of Phyllanthus amarus ethanolic extract on various biochemical parameter's in the brain of arsenic administered Wistar albino rats. Methodology: The neuroprotective activity of P. amarus against arsenic induced toxicity was studied in Wistar albino rats. The experimental animals (n=24) were divided into four groups of 6 rats each. Rats in group I received distilled water, whereas rats in groups II, III, and IV received arsenic as sodium arsenite salt (40 mg/kg b.w) in drinking water daily for 28 days. In addition, rats from groups III, and IV also received P. amarus ethanolic extract 100 and 200 mg/kg b.w, by intragastric route, once daily for a period of 28 days. At the end of the experiment rats were subjected to various neurobehavioral tests such as Elevated plus maze, Light dark arena, Forced swim test and Tail suspension test. After 24 h of the last treatment, the animals were euthanized and brain tissue was assayed for various biochemical parameters. Results: ANOVA and Post hoc testing of behavioral and biochemical data (Dunnett's t-test and Student unpaired T test) showed co-administration of P. amarus ethanolic extract significantly reversed anxiety and depression-like behaviors in experimental animals. P. amarus ethanolic extract effectively reduced acetyl cholinesterase activity in the brain, and it also increased the levels of dopamine and serotonin in the brains of arsenic-treated animals as compared to only arsenic treated group. P. amarus ethanolic extract significantly decreased lipid peroxidase and increased brain catalase and super oxidase dismutase activities. Conclusion: Based on the pharmacological, and biochemical analysis the plant extracts of P. amarus have shown protective effects against arsenic induced neurotoxicity.